ANALYSIS OF MEAT CHEMICAL COMPOSITION AND FISH MEAL FROM SNAKEHEAD FISH (Channa striata) - Nadia Mahardika; Rahman Karnila; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to find out the meat and fish meal proximate composition from snakehead fish (Channa striata). The study consists of 2 stages: 1) Preparation and making of a snakehead fish meal, 2) Proximate analysis of snakehead fish meat and fish meal. The parameter that observed in the stage 1 were the yield of meat and fish meal of snakehead, in the stage 2 were water content, ash content, protein content, fat content, and carbohydrate content (by different). The results showed that snakehead fish meat with a yield 31.41% and snakehead fish meal with a yield 12,46%. Chemical composition that produced from snakehead fish meat were water content 75.35% (gw), ash content 6.89% (dw), protein content 78.38% (dw), and fat content 4.54% (dw). Chemical composition that produced from snakehead fish meal were water content 5.68% (gw), ash content 6.29% (dw), protein content 86.31% (dw), and fat content 5.27% (dw). Keywords: Snakehead Fish, Yield, Chemical Composition Keywords: Snakehead Fish, Yield, Chemical Composition